2017
DOI: 10.1016/j.ijpsycho.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide association study of fast beta EEG in families of European ancestry

Abstract: BACKGROUND Differences in fast beta (20–28 Hz) electroencephalogram (EEG) oscillatory activity distinguish some individuals with psychiatric and substance use disorders, suggesting that it may be a useful endophenotype for studying the genetics of disorders characterized by neural hyper-excitability. Despite the high heritability estimates provided by twin and family studies, there have been relatively few genetic studies of beta EEG, and to date only one genetic association finding has replicated (i.e., GABRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 95 publications
(122 reference statements)
0
16
0
Order By: Relevance
“…GWASs and quantitative trait loci mapping studies in COGA and other large‐scale alcoholism cohorts have identified numerous disease‐associated loci (Clarke et al., ; Meyers et al., ). The most‐replicated alcohol dependence–related genes include ADH1B ( in European and African‐ancestry subjects ) and ALDH2 ( in Asians ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GWASs and quantitative trait loci mapping studies in COGA and other large‐scale alcoholism cohorts have identified numerous disease‐associated loci (Clarke et al., ; Meyers et al., ). The most‐replicated alcohol dependence–related genes include ADH1B ( in European and African‐ancestry subjects ) and ALDH2 ( in Asians ).…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalograms (EEG) are promising, noninvasive functional brain phenotypes used to study neurophysiological effects of chronic alcohol abuse and withdrawal, both at rest (resting EEG) and during cognitive paradigms (event‐related potentials and oscillations; Rangaswamy and Porjesz, ). Because resting EEG is relatively stable throughout healthy adult life and highly heritable (Tang et al., ), it is used to study chronic alcoholics and their offspring (Begleiter and Porjesz, ; Rangaswamy and Porjesz, ), including earlier linkage and association genetic studies (Edenberg et al., ), and more recently with genomewide association (GWA; Meyers et al., ; Smit et al., ).…”
mentioning
confidence: 99%
“…Current sample sizes may be adequate to reveal significant individual genetic associations, pathways for the expression of psychiatric liability in the brain, and prove hopeful for future GWAS of additional EEG parameters. For example, two recently published GWASs of bipolar EEG from families of African and European ancestry reported genome-wide signal at 3q26 and 6q22, respectively 31,80…”
Section: Genetic Correlation Analysismentioning
confidence: 99%
“…In addition, the power of the arousal-indicating EEG frequency bands was observed with heritabilities of 80% [29]. To date, there have been four GWAS on resting state EEG activity [29][30][31][32]. However, none has assessed arousal and its regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we conducted a GWAS catalog screening and queried our top hits in the Psychiatric Genomics Consortium data files. In addition, we derived candidate markers from the four GWAS on other resting EEG activity traits [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%